Programmable controllers an engineer's guide - Parr, E. A. (E. Andrew) (Oxford ; Burlington, MA : Newnes, 2003)
Andrew Parr's Programmable Controllers provides a thoroughly practical introduction to the use of PLCs in industry, covering programming techniques alongside systems-level design issues. In the third edition a masterclass series of real-world case studies have been added to illustrate typical engineering challenges - and model solutions. New material also includes the new IEC-61508 functional safety standard, use of Windows-based software on programming terminals, an expanded section on Scada, and extended coverage of networks and fieldbus. Andrew Parr works at ASW Sheerness Steel where the plant control is based on approximately sixty programmable controllers. * The practical guide to PLC applications for engineers and technicians * Systems-level design and control covered alongside programming techniques * Coverage matched to introductory college programs.
Preface; Computers and industrial control; Programming techniques; Programming style; Analog signals, closed loop control and intelligent modules; Distributed systems; The man machine interface; Industrial control with conventional computers; Practical aspects; Smaple ladder logic; Appendix; Index.
Previous ed.: 1999.
Includes index.
Keywords: Programmable controllers; Automatic control -- Computer programs; Process control -- Computer programs; Electronic books